Tipe Parental Mediation dan Adiksi Internet Siswa Kelas V SD X Bandung - Mega Mutiara Nur Arrofah Wita; Andhita Nurul Khasanah; Makmuroh Sri Rahayu (Psympathic : Jurnal Ilmiah Psikologi, 2018)
The purpose of this study was to examine the correlation between parental mediation and addiction in late childhood. Participants of this research were sixty 5th-grade primary school students in Bandung. The instruments were questionnaire compiled based on the theory of Parental Mediation from Livingstone (2008) and Internet Addiction from Griffith (2015) and depth interview on some parents. The data was analyzed using the Spearman Rank. The findings showed that there was a correlation between parental mediation and internet addiction. Parents used mediation behavior to reduce children's internet activity. However, the children perceived it has no impact on them.